2022
DOI: 10.1038/s41377-022-01004-2
|View full text |Cite
|
Sign up to set email alerts
|

Optically-generated focused ultrasound for noninvasive brain stimulation with ultrahigh precision

Abstract: High precision neuromodulation is a powerful tool to decipher neurocircuits and treat neurological diseases. Current non-invasive neuromodulation methods offer limited precision at the millimeter level. Here, we report optically-generated focused ultrasound (OFUS) for non-invasive brain stimulation with ultrahigh precision. OFUS is generated by a soft optoacoustic pad (SOAP) fabricated through embedding candle soot nanoparticles in a curved polydimethylsiloxane film. SOAP generates a transcranial ultrasound fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 52 publications
(80 reference statements)
1
27
0
Order By: Relevance
“…The mechanical index of the PA stimulation was found to be less than 1, below the FDA-approved value of 1.9 (FDA-2017-D-5372). Experimentally, our results have confirmed no tissue damage observed in vivo used in the photoacoustic brain stimulation. , …”
Section: Remaining Challenges and Outlooksupporting
confidence: 81%
See 1 more Smart Citation
“…The mechanical index of the PA stimulation was found to be less than 1, below the FDA-approved value of 1.9 (FDA-2017-D-5372). Experimentally, our results have confirmed no tissue damage observed in vivo used in the photoacoustic brain stimulation. , …”
Section: Remaining Challenges and Outlooksupporting
confidence: 81%
“…The PA approach offers the merits of being non-contacting with a high penetration depth via ultrasound as well as high spatial precision and multiplexing capacity via photons. Enabled by chemical synthesis and material design, we have designed different materials and devices as highly efficient PA transducers, including fiber-based photoacoustic emitters, ,, PA films, PA nanoparticles, and optically driven focused ultrasound . They have been applied as implants minimally invasive, and noninvasive neural interfaces for different applications.…”
Section: Introductionmentioning
confidence: 99%
“…Photoacoustic nanoparticles represent a less invasive alternative, although the penetration depth of 1030 nm light remains limited in biological tissue . The use of injections or implants may be overcome by the externally placed optoacoustic transducers; however, this method lacks the spatial precision of the FOC and PAN technologies …”
Section: Neuromodulation Methods With Mechanical Force As the Seconda...mentioning
confidence: 99%
“…19 The use of injections or implants may be overcome by the externally placed optoacoustic transducers; however, this method lacks the spatial precision of the FOC and PAN technologies. 70 Besides photoacoustic neuromodulation, the interaction of light with molecules that undergo photoisomerization upon irradiation offers a fundamentally different mechanism to mechanically modulate neural activity. This mechanism, which is known as photoswitchable molecular actuation, is based on a well-known phenomenon in which the mechanical perturbation of membranes can modulate neural activity by directly modifying the membrane potential.…”
Section: Photoacoustic and Photoswitchable Molecular Actuationmentioning
confidence: 99%
“…In 2020, Jiang et al reported the development of a fiber optoacoustic emitter 14 capable of sub-millimeter neurostimulation both in vitro and in vivo. In addition to the fiber device, other modalities were also developed for different applications, including biocompatible optoacoustic films for neural regeneration 15 , photoacoustic nanotransducers 16 for single cell stimulation, and optically generated focused ultrasound for transcranial brain stimulation 17 .…”
Section: Introductionmentioning
confidence: 99%